2018
DOI: 10.1002/acr.23477
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Slower Walking Speed and T1ρ Magnetic Resonance Imaging of Femoral Cartilage Following Anterior Cruciate Ligament Reconstruction

Abstract: Slower walking speed at 6 and 12 months following ACLR may be associated with early proteoglycan density changes in medial femoral compartment cartilage health in the first 12 months following ACLR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 47 publications
2
69
3
Order By: Relevance
“…Even though walking speed decline was associated with worsening BML and effusion volume in individuals who developed accelerated knee OA, there was no significant association between walking speed decline and knee articular cartilage change in any group. While we observed no significant association between walking speed and articular cartilage, results from prior cross‐sectional studies and prognostic studies have suggested a link between walking speed and cartilage health . Specifically, slower walking speed is significantly associated with worse cartilage composition (i.e., T1rho relaxation times) as well as with serum biomarkers of cartilage metabolism (i.e., the ratio of type II collagen degradation to synthesis) in individuals at high risk of knee OA (i.e., young adults with a history of an anterior cruciate ligament reconstruction).…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Even though walking speed decline was associated with worsening BML and effusion volume in individuals who developed accelerated knee OA, there was no significant association between walking speed decline and knee articular cartilage change in any group. While we observed no significant association between walking speed and articular cartilage, results from prior cross‐sectional studies and prognostic studies have suggested a link between walking speed and cartilage health . Specifically, slower walking speed is significantly associated with worse cartilage composition (i.e., T1rho relaxation times) as well as with serum biomarkers of cartilage metabolism (i.e., the ratio of type II collagen degradation to synthesis) in individuals at high risk of knee OA (i.e., young adults with a history of an anterior cruciate ligament reconstruction).…”
Section: Discussioncontrasting
confidence: 69%
“…While we observed no significant association between walking speed and articular cartilage, results from prior cross‐sectional studies and prognostic studies have suggested a link between walking speed and cartilage health . Specifically, slower walking speed is significantly associated with worse cartilage composition (i.e., T1rho relaxation times) as well as with serum biomarkers of cartilage metabolism (i.e., the ratio of type II collagen degradation to synthesis) in individuals at high risk of knee OA (i.e., young adults with a history of an anterior cruciate ligament reconstruction). Additionally, habitual walking speed is associated with acute femoral cartilage deformation following a 30‐minute treadmill walk , indicating that walking speed may play a role in cartilage loading that is important in the maintenance of cartilage health.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Recent data suggests that slower habitual walking speeds at 6 months post ACLR are associated with greater T1ρ MRI relaxation times (i.e. lesser proteoglycan density) at 12 months following ACLR [41]. Additionally, slower walking speeds in a cohort of ACLR patients, at an average of 43 months post-ACLR, demonstrated greater serum biomarker concentrations of type II cartilage breakdown [46].…”
Section: Magnetic Resonance Imaging For Assessing Early Posttraumaticmentioning
confidence: 99%
“…However, these techniques are expensive, technically demanding, generally investigational, and inaccessible to many clinicians. Measures such as habitual walking speed, 156,157 quadriceps strength (normalized to total body mass), 128 and patient-reported outcomes 158 show promise as clinically relevant measures associated with early changes in joint tissue health after ACLR.…”
Section: Return-to-play Considerations After Aclrmentioning
confidence: 99%